Pembuatan Animasi Aset 3D dalam Film Pendek Gugu si Gonggong Ajaib sebagai Media Promosi UMKM Menggunakan Blender 3D - Aqid, Aizudin; indonesia, indonesia (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
The development of digital technology opens up new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to increase their competitiveness through 3D animation-based promotional media. This study aims to design and animate 3D assets in the short film "Gugu si Gonggong Ajaib" as a promotional media for MSMEs in the Riau Islands using Blender 3D software. The research method used is a qualitative method with a product design approach, which consists of three main stages, namely pre-production, production, and post-production. In the pre-production stage, story idea development, storyboard creation, character design, and environmental design are carried out. The production stage includes modeling, texturing, rigging, animation, lighting, and rendering of 3D assets. While the post-production stage includes compositing and video editing. The result of the study is a 1 minute 13 second animated video with a resolution of 1920 × 1080 pixels (Full HD), which displays local characters with an attractive visual approach to support MSME product promotion. The application of 3D animation has been proven to increase visual appeal, strengthen product image, and expand the reach of digital promotions. This research is expected to be a reference for MSMEs and digital content creators in utilizing 3D animation as an innovative promotional medium.